Placental morphology, apoptosis, angiogenesis and epithelial mechanisms in early-onset preeclampsia. (March 2019) - Travaglino, Antonio; Raffone, Antonio; Saccone, Gabriele; Migliorini, Sonia; Maruotti, Giuseppe Maria; Esposito, Gennaro; Mollo, Antonio; Martinelli, Pasquale; Zullo, Fulvio; D'Armiento, Maria
Abstract: Objectives: Early-onset preeclampsia is a form of preeclampsia requiring delivery before 34 weeks of gestation. The etiology is unknown, but placental dysfunction appears crucial. We evaluated the immunohistochemical expression of the antiapoptotic protein Bcl-2, the angiogenetic factors VEGF and PlGF, and the epithelial factors HGF, c-Met and STAT3 in placental samples of pregnancies complicated by early-onset preeclampsia. Materials and methods: Placental sections were obtained from 41 women with early-onset preeclampsia (cases) and from 31 uncomplicated pregnancies (controls). A standard haematoxylin and eosin stain was used to assess histological structure. Immunohistochemical expression of Bcl-2, VEGF, PlGF, HGF, c-Met and STAT3 was analyzed. Results: Mean gestational age was 32 weeks in cases and 39 weeks in controls. Microscopically, sections from women with preeclampsia showed a disorder of villous development as a distal villous hypoplasia with placental undergrowth. The immunoistochemical expression of Bcl-2 (p < 0.0001), VEGF (p = 0.0323), PlGF (p = 0.002), HGF (p < 0.0001), c-Met (p < 0.0001) and STAT3 (p = 0.0004) were significantly lower in placentas of complicated pregnancies compared to uncomplicated ones. Conclusions: Early-onset preeclampsia is associated with a disorder of villous development. Apoptotic, angiogenetic and epithelial mechanisms are simultaneously impaired and contribute to placental dysfunctions.